Isolated renal pelvis rupture due to blunt trauma presenting with low-density fluid accumulation around kidney on initial CT: A case report - Yukiko Asanuma; Motoo Fujita; Tomomi Sato; Takuma Sato; Shigeki Kushimoto (Trauma Case Reports, 2025)
Back ground: Renal pelvis rupture due to trauma is commonly diagnosed in an excretory phase CT scan, which is not be applied in substantial proportion of trauma patients during initial evaluation. Since renal pelvis rupture has no specific findings, there is no clear indication to perform an excretory phase CT scan in the evaluation of trauma patients. We experienced a case presented with low-density fluid accumulation around kidney on plain CT imaging, subsequently diagnoses as having isolated renal pelvis injury. Case presentation: 68-year-old male fell from the second floor and referred to our institution. He had pain in his left buttock with a subcutaneous hematoma. He presented as blood pressure of 155 mmHg, heart rate of 145 beats/min, and blood test showed no specific abnormalities. Plain CT showed fluid accumulation around the left kidney, and following a contrast-enhanced CT scan at equilibrium phase showed no urinary extravasation. On the 4th hospital day, he complained of worsening back pain, and excretion phase of contrast-enhanced CT revealed left renal pelvic rupture. We placed a double-J ureteral stent for urinary drainage. Thereafter, disappearance of urinary extravasation without ureteral stricture was confirmed. Conclusion: In patients with blunt trauma, perirenal effusion collection inconsistent with hemorrhage on CT imaging could be considered as a sign of isolated renal pelvic rupture.